Fatores relacionados à resposta inadequada da pressão arterial pulmonar imediatamente após a Valvoplastia Mitral Percutânea - Igor Ferreira de Sales (2019)
Introduction: Pulmonary hypertension (HP) has long been known to be a marker of poor outcome in patients with mitral stenosis (MS). Percutaneous mitral valvuloplasty (PMV) is currently the treatment of choice for MS, which results in improvement in HP. However, despite the successful valve opening a, the regression of PH may be incomplete. This has been attributed to irreversible morphologic changes within the pulmonary vasculature. Therefore, this study was design to assess the factors related with an inadequate response of the pulmonary artery pressure immediately after a successful PMV, and also the impact of residual PH on long-term outcome in these patients. Methods: One hundred eighty-one patients submitted to the PMV for symptomatic rheumatic MS between April 2011 and July 2018 were enrolled. All patients recruited underwent an echocardiographic and invasive hemodynamic evaluation before and immediately after the mitral valvuloplasty procedure. After the PMV, the patients were divided into two groups. Group 1: Decrease in mean pulmonary artery pressure (mPAP) immediately after the procedure; group 2: Unchanged mPAP after PMV. The objective was to identify the factors related to abnormal blood pressure response after the procedure and to assess whether inadequate response could predict adverse events at follow-up. Results: Of the 171 patients analyzed, 52 (30%) did not present reduction of mPAP immediately after the PMV. The mean age was 44.1 12.6 years, and 157 patients were women (86.7%). Mitral valvuloplasty had previously been performed in 27 patients (15%), including either percutaneous or surgical intervention. In the overall population, (mPAP) decreased from 33.4 ± 13.1 before to 27.6 ± 9.8 mmHg (p<0.001) as mitral valve increased from 0.96 ± 0.2 before to 1.68 ± 0.2 (p<0.001) immediately after PMV. Transmitral pressure gradients were significantly greater and mitral valve area was smaller in those patients with unchanged mPAP after PMV than in those whose pulmonary pressures had decreased. Systolic, diastolic and mPAP pressures as well as left atrial pressure were higher in those patients who had improvement in pulmonary pressures after PMV. Multivariate analysis revealed the following independent predictors of unchanged pulmonary artery pressure :atrial fibrillation (OR 2.7, 95% CI 1.1 to 6.4), mitral valve area (OR 1.3, 95% CI 1.1 to 1.5), maximum leaflets displacement (OR 0.8, 95% CI 0.7 to 0.9), and left ventricular compliance after PMV (OR 0.8, 95% CI 0.6 to 0.9). During a mean follow-up period of 28 months , adverse outcomes was reached in 48 patients (26%). The pulmonary pressure response to PMV was not predictor of long-term events. Conclusion: The results of this study allow us to identify the factors related to the incomplete pulmonary artery pressure response in patients submitted to PMV. During follow-up, this inadequate PH response was not able to predict a tendency for poor outcomes